Estudo dos riscos relativos à estrutura organizacional em implantações de Lean Production: um estudo de caso integrado em unidades de negócio manufatureiras de uma empresa multinacional - Farhat, Daniel Madazio Rahal (2016)
Nowadays there are many methods and techniques proposed for the implementation of Lean Production, and there are several risks identified in studies that influence the success of these implementations. However, little is said about the relationship of these risks with changes in organizational structures and how they are treated during the implementations. This work, performed in business units of a large multinational company, aims to identify, according to the implementation responsible, the risks related to the elements of the organizational structure that may be associated with Lean Production implementations, as well as to check whether they were considered during the structuring and execution of the implementation projects. The study was based on an integrated case study in four units located in Brazil, which passed through distinct Lean Production implementation projects. An amount of 101 different risks related to the elements of organizational structures was identified and associated with Lean Production implementations in the four business units, as well as it can be seen that 31 of them are patterns between at least two of the four units. Seeking for standard risks among the four units, just the threat of a culture resistant to change and the opportunity of the training in Lean Production application were found. Such evidence clearly shows that these four business units belonging to the studied company had each other different types of risks related to the organizational structure associated with the implementations. A small portion of these risks, mostly opportunities, was considered during the design of the project, but still not using a systematic or standardized way, and most of the risk is not identified or at design or during project execution, but rather treated as becomes a real difficulty for the achievement of the results of project implementation.